Populism: consequences for global sustainable development - Paul Marschall; Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Populism is a style of politics that attacks the existing normative consensus within society, making systematic use of marginalisation and bogeyman tactics. Typical marginalisation strategies target minorities within the population and adopt an anti-scientific world view. Restrictions on civil society are one of the consequences of government action dominated by populism. When it comes to mobilising voters, populists draw upon selected topics which differ according to political camp (left-wing versus right-wing populism) and national context. Nonetheless, it is possible to identify certain patterns of populist expression, such as the practice of contrasting the “people” and their supposed will with an allegedly out-of-touch political “elite”. The values of the population are largely set within the national context, while representatives of the elite are often portrayed as primarily interested in interactions outside of the nation state and thus perceived and characterised as proponents of globalisation. Populist trends can be seen in Western nations, former Eastern Bloc states and countries in the global South. Populist movements pose considerable threats to multilateral efforts aimed at tackling transnational political challenges. These patterns include: Abandonment of efforts to promote integration. Accordingly, the European Union (EU) is considered an “elite project” and emblematic of many of the negative aspects of globalisation. Abandonment of multilateral institutions and inter¬na¬tional trade agreements. This includes withdrawal from international accords (Paris climate agreement, etc.) and international organisations. Reinterpretation/rejection of development policy. Development policy is not understood as an original instrment for promoting global sustainable development, but rather reinterpreted as a vehicle for achieving narrow national goals. The partially transnational nature of populism could present an additional challenge for global sustainable development in future. Efforts by populist streams to cooperate at cross-border level and thus create a form of “meta-populism” have barely succeeded to date, but this could change after the European elections in May 2019. The current and the expected future significance of populist actors varies from country to country. Even in nations in which populists are not currently in government, the state could introduce budget cuts or reallocate funding to specific development policy topics in an effort to minimise the electoral gains of the populists. This runs the threat of populist approaches becoming effective even in countries where populist parties are not in government.
Keywords: 330; Demokratie und Autokratie; Deutsche + Europäische + multilaterale Entwicklungspolitik